DEVELOPMENT of TRADITIONAL FOOD PRODUCT INNOVATION from an OPERATIONAL POINT of VIEW - Eric Harianto; Tania Susanti; Riduan Mas'ud; Nursaid Nursaid; Denpharanto Agung Krisprimandoyo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Increasingly tight competition in the snack industry today so many new snacks are produced and packed with modern packaging causing the eroding of the traditional food industry, including bipang. In addition, changes in people's consumption patterns, Covid-19 pandemic and the existence of the concept of industry 4.0 require the traditional food industry to be more active in the development of innovation. This research was conducted from September 2021 until January 2022 using qualitative methodology with Blue Ocean Strategy approached by interviewing individuals who are working and customers of Bipang Pak Tani Pasuruan, also used relevant books, journals, and websites. Data testing has been done with triangulation method. The results of this study are: 1) Strategy Canvas that helps Bipang Pak Tani understand the strength and weakness compared to its competitors, 2) ERRC matrix where Bipang Pak Tani can simultaneously eliminate, reduce, raise and create factors that offered as an effort to differentiate and reduce costs so as to create value innovation by making a new strategic profile, 3) Bipang Pak Tani can reconstruct industry boundaries by doing across chain of buyers. In this research, finally found a new innovation strategy are rebranding products with new concept product (packaging, size and varians) also marketing innovation by doing online marketing.